Activation of the Nrf2/ARE signaling pathway ameliorates hyperlipidemia-induced renal tubular epithelial cell injury by inhibiting mtROS-mediated NLRP3 inflammasome activation - Jiang, Xu-shun; Liu, Ting; Xia, Yun-feng; Gan, Hua; Ren, Wei; Du, Xiao-gang (Frontiers in Immunology, 2024)
Dyslipidaemia is the most prevalent independent risk factor for patients with chronic kidney disease (CKD). Lipid-induced NLRP3 inflammasome activation in kidneyresident cells exacerbates renal injury by causing sterile inflammation. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor that modulates the cellular redox balance; however, the exact role of Nrf2 signalling and its regulation of the NLRP3 inflammasome in hyperlipidaemia-induced kidney injury are poorly understood. In this study, we demonstrated that activation of the mtROS-NLRP3 inflammasome pathway is a critical contributor to renal tubular epithelial cell (RTEC) apoptosis under hyperlipidaemia. In addition, the Nrf2/ARE signalling pathway is activated in renal tubular epithelial cells under hyperlipidaemia conditions both in vivo and in vitro, and Nrf2 silencing accelerated PA-induced mtROS production, mitochondrial injury and NLRP3 inflammasome activation. However, the activation of Nrf2 with tBHQ ameliorated mtROS production, mitochondrial injury, NLRP3 inflammasome activation and cell apoptosis in PA-induced HK-2 cells and in the kidneys of HFD-induced obese rats. Furthermore, mechanistic studies showed that the potential mechanism of Nrf2-induced NLRP3 inflammasome inhibition involved reducing mtROS generation. Taken together, our results demonstrate that the Nrf2/ARE signalling pathway attenuates hyperlipidaemia-induced renal injury through its antioxidative and anti-inflammatory effects through the downregulation of mtROSmediated NLRP3 inflammasome activation.